Live or death in cells: from micronutrition metabolism to cell fate - Wang, Yuting; Wu, Wei; Gong, Jianke (Frontiers in Cell and Developmental Biology, 2023)
Nutrients have strong relationship with cell death and both are essential for human to maintain good body health. Dysregulation of any nutrient causes metabolic or chronic diseases, including obesity, cardiometabolic condition, neurodegeneration, and cancer. The nematode Caenorhabditis elegans is an ideal genetic model for studying the mechanisms of nutrient in metabolism, healthspan and lifespan. For example, C. elegans is a haem auxotroph, the research of this special haem trafficking pathway contributing important reference to mammal study. Also, the simple anatomy, known cell lineage, well-established genetics and easily distinguishable cell morphology make C. elegans a powerful model for studying the mechanisms of cell death including apoptosis, necrosis, autophagy, and ferroptosis. Here, we present the current understanding of nutrient metabolism and also discuss the fundamental mechanisms of different kinds of cell death. A thorough understanding of these physiological processes not only builds a foundation for developing better treatments for various nutrient disorders, but also provides key insights into human health and aging.